'Samoa - BD researches kept in Theological College, Fiji'
Includes draft chapters from a [thesis?] on the Congregational Christian Church of Samoa (CCCSA), used as a case study; questions for the Samoan Churches [from Andrew Prasad]; lists of 'B.D. Project Reports' detailing studies made on Samoa, with authors and dates; copies of chapters from various theses on the church, theology and mission in Samoa, including full copy of 'A Historical Analysis of the Schism between Congregational Christian Church in Samoa and the Congregational Church in American Samoa', by Saneterini Amosa, Nov 1991 (project report, The Pacific Theological College); copy of report of CWM Personnel Exchange visit to Samoa, 1999.